Teachers Role in Preschoolers' Development - Yunus, Saima; Munir, Fahad (2025)
Teaching children from being nascent to eight years old is of paramount emphasis in the field of early childhood education. Preparing these young fellows for kindergarten and developing their personality is one aspect of early childhood education. It seeks to offer a strong and comprehensive foundation for learning and wellbeing throughout life by attending to each child's physical, social, emotional, cognitive, and linguistic requirements. Teachers are crucial to a child's formal educational development hereby, play a critical role in a child's formal educational development. One facet of early childhood education is preparing children for primary school; it aims to provide a solid and all-encompassing foundation for learning and wellbeing throughout life by attending to each child's physical, social, emotional, cognitive, and linguistic needs.